Good boundaries and goodbyes eaudiobook Loving others without losing the best of who you are. - TerKeurst, Lysa (Thomas Nelson, 2022)
2024 ECPA CHRISTIAN BOOK AWARD - AUDIOBOOK OF THE YEAR READ BY THE AUTHOR Relationships are wonderful . . . until they're not. Stop the dysfunction of unhealthy relationships and learn biblical ways to set boundaries—and, when necessary, say goodbye. Is it unloving or selfish to set a boundary with family members or friends? Are Christians ever called to walk away from a relationship that's no longer safe or sustainable? #1 New York Times bestselling author Lysa TerKeurst deeply understands these hard questions in the midst of relational struggles. After thousands of hours of counseling intensives and extensive theological research that transformed the way she defined healthy relationships, Lysa is now more committed than ever to loving people well without losing the best of who she is. In these pages, Lysa will help you: Understand the five factors to remember when implementing healthy boundaries. Determine the appropriate amount of personal and emotional access someone has to you. Stop being misled and emotionally paralyzed by wrongly interpreted or weaponized Bible verses that perpetuate unhealthy relationships. Be equipped with effective boundary-setting tools, such as realistic scripts and practical strategies for healthier communication. Be empowered to say goodbye without guilt when a relationship has shifted from difficult to destructive. Receive therapeutic wisdom you can trust directly from Lysa's Christian counselor Jim Cress, who weighs in throughout the book. You'll be relieved to learn that boundaries aren't just a good idea, they're a God idea. Look for additional biblically based resources and devotionals from Lysa: Forgiving What You Can't Forget It's Not Supposed to Be This Way Uninvited You're Going to Make It Embraced Seeing Beautiful Again